Ni-based bimetallic surface alloy catalysts for enhanced poisoning resistance in steam methane reforming: A combined DFT and experimental study - Cha, Hwa-Woong; Song, Giseong; Min, Kyeongseok; Akpe, Shedrack G.; Kim, Junseong; Yoon, Sung Pil; Baeck, Sung-Hyeon; Ham, Hyung Chul (Elsevier, 2025)
This study investigates the activities of Ni-M (M = transition metals) bimetallic catalysts in Molten Carbonate Electrolysis Cells (MCEC) for hydrogen production via steam methane reforming (SMR) under electrolyte poisoning conditions by using the density functional theory (DFT) and experimental approach. Focusing on the cost-effective and high-activity Ni (211) catalyst, the study addresses the challenge of electrolyte (Li2CO3, K2CO3) evaporation leading to catalyst deactivation. Utilizing DFT, we examined partially electrolyte-poisoned Ni (211) slab models, particularly assessing potassium (K) atom effects. The study proposes bimetallic Ni-M surface alloy catalysts, such as Ni-V, demonstrating enhanced electrolyte poisoning resistance and superior catalytic activity compared to pure Ni. The findings highlight the potential of these catalysts to improve MCEC system efficiency, offering a more economical alternative to precious metal catalysts.